Installation of AutoDELFIA: A new addition in Bangladesh for the Screening of Congenital Hypothyroidism in Newborn Babies (Bangladesh Journal of Nuclear Medicine, 2022)
Newborn Screening for the diagnosis of Congenital Hypothyroidism (CH) was first started in Bangladesh in 1999 by the Immunoradiometric assay (IRMA). Dissociation enhanced lanthanide fluorescent immunoassay (DELFIA) was started in 1986 due to its superior sensitivity, speed, and non-radioactive methodology. Auto DELFIA 1235 automatic immunoassay system was introduced in the In vitro Division of National Institute of Nuclear Medicine & Allied Sciences (NINMAS) under the ADP Project “Screening of Congenital Hypothyroidism in Newborn Babies (Phase 2)”. It is an automatic system that can minimize the pipetting error. In this experiment, dried blood spots (DBS) were punched into an antibody-coated microtitration well with an automated Panthera Puncher and analyzed by AutoDELFIA. Six different standards of 0.8, 10.3, 24.5, 49.3, 93.2, 239μU/mL were used and the calibration curve was drawn by using these standards. Standard error and Standard deviation were found 12.4 and 30.5. Limit of detection (LOD) and Limit of Quantification (LOQ) of X variables were 0.16 and 0.47. The average of the percent recovery was 96.7. The R2 value of the calibration curve was 0.9985. The accuracy of the standard samples was 96.7 ±10.6. For this assay two Quality Control (QC) of 16.39 μU/mL and 63.09, μU/mL were used. All of the measured values from the calibration curve were close to ±1 standard deviation. All these findings indicate appropriateness of Auto DELFIA System for the CH screening from dried blood spots in the newborn screening laboratory of the In vitro division of NINMAS.Bangladesh J. Nuclear Med. 23(1&2): 15-20, 2020